RUSSIA IN THE EDUCATIONAL INTEGRATION OF THE ASIA- PACIFIC REGION - Tatyana L. Guruleva (Высшее образование в России)
The article is devoted to the processes of formation of educational space of the Asia2Pacific region. It describes the participation of Russia in cooperation in the region in the field of higher education, recommendations for further integration of our country into the educational processes that take place in Asia and for the successful formation of a common educational space of the Asia2Pacific region.